Geofluid Systems of Koryaksky-Avachinsky Volcanoes (Kamchatka, Russia) - A. Kiryukhin; V. Lavrushin; P. Kiryukhin; P. Voronin (Geofluids)
The Koryaksky-Avachinsky volcanogenic basin, which has an area of 2530 km2, is located 25 km from Petropavlovsk-Kamchatsky City and includes five Quaternary volcanoes (two of which, Avachinsky (2750 masl) and Koryaksky (3456 masl), are active), and is located within a depression that has formed atop Cretaceous basement rocks. Magma injection zones (dikes and chamber-like shapes) are defined by plane-oriented clusters of local earthquakes that occur during volcanic activity (mostly in 2008–2011) below Koryaksky and Avachinsky volcanoes at depths ranging from −4.0 to −2.0 km and +1.0 to +2.0 km, respectively. Water isotopic (δD, δ18O) data indicate that these volcanoes act as recharge areas for their adjacent thermal mineral springs (Koryaksky Narzans, Isotovsky, and Pinachevsky) and the wells of the Bystrinsky and Elizovo aquifers. Carbon δ13С data in СО2 from CO2 springs in the northern foothills of Koryaksky Volcano reflect the magmatic origin of CO2. Carbon δ13С data in methane CH4 reservoirs penetrated by wells in the Neogene-Quaternary layer around Koryaksky and Avachinsky volcanoes indicate the thermobiogenic origin of methane. Thermal-hydrodynamic TOUGH2 conceptual modeling is used to determine what types of hydrogeologic boundaries and heat and mass sources are required to create the temperature, pressure, phase, and CO2 distributions observed within the given geological conditions of the Koryaksky-Avachinsky volcanic geofluid system.